Global analysis of the environmental management of hazardous industrial wastes: systematic and bibliometric review - Bedoya Rodríguez, Francisco Javier; Hurado Sánchez, Alejandro; Ibagón Bravo, Andrés Felipe (Ingeniería Solidaria, 2025)
Introduction: This article presents research on the sustainable management of hazardous industrial waste, based on a systematic and global bibliometric review conducted at Fundación Universitaria de Popayán in 2024.Problem: Inadequate management of hazardous industrial waste poses significant risks to both health and the environment, highlighting the urgent need to integrate sustainable practices and circular economy principles into waste management strategies.Objective: The study aims to perform a systematic review and bibliometric analysis of global research on hazardous industrial waste management, identifying key trends and innovative technologies.Methodology: Following the PRISMA guidelines to ensure transparency, the review is complemented by bibliometric analysis using Vosviewer software.Results: The literature on hazardous industrial waste management has grown, with particular focus on the metallurgical industry and sustainable approaches. China and India are leading contributors, although publication rates declined between 2016 and 2019 due to shifts in research priorities.Conclusion: The study emphasizes the critical role of adopting circular economy practices in hazardous waste management and the need to strengthen international collaboration to effectively address environmental challenges.Originality: This systematic review offers a comprehensive knowledge matrix on hazardous industrial waste management, underscoring emerging trends toward circular economy adoption and sustainable practices.Limitations: Limitations include the scope of the review, which could be expanded in future research by including additional databases such as Web of Science alongside Scopus and Google Scholar for a more exhaustive analysis.
Keywords: hazardous industrial waste; waste management; waste disposal; circular economy; bibliometric study